Matrix isolation study of the early intermediates in the ozonolysis of selected vinyl ethers. Issue 31 (31st March 2017) - Lv, Chen; Du, Lin; Tang, Shanshan; Tsona, Narcisse T.; Liu, Shijie; Zhao, Hailiang; Wang, Wenxing
Abstract : The Criegee mechanism of the ozonolysis reaction of vinyl ethers has been observed by matrix isolation FTIR spectroscopy. Abstract : The matrix isolation technique combined with infrared spectroscopy has been used to characterize Criegee Intermediates (CI) and other products formed during the ozonolysis reactions of ethyl vinyl ether and n -butyl vinyl ether. Twin jet deposition at 14 K led to a number of new bands indicating the formation of products, with an intensity increase of ∼150% to 400% when annealing to 30 K. All the infrared absorptions could be assigned to different bands, which provided direct evidence for the formation of primary ozonides, CI and secondary ozonides in the systems investigated. Theoretical calculations at the B3LYP-D3/aug-cc-pVTZ level were carried out to complement the experimental observations. Experimental and theoretical results demonstrate that the studied ozonolysis reactions predominantly follow the Criegee mechanism. The current results will allow a better assessment of the potential environmental impacts of vinyl ethers.